Antidiabetic and antioxidant activities of two alpine species of Swertia L. - Thapa, Laxmi; Chaturwedi, Shashi Bhushan; Joshi, Giri Prasad; Pant, Deepak Raj (Nepal Journal of Botany, 2024)
Species of Swertia L. from alpine areas are used for the treatment of various ailments in ayurvedic and Tibetan medicine. The present work has attempted to assess the antidiabetic and antioxidant activity of the methanol extracts from aerial parts of two species of Swertia, S. barunensis and S. multicaulis from alpine areas of Nepal. The study has also attempted to compare the liquid chromatography mass spectrometry (LC-MS) analysis of their methanol extracts. LC-MS analysis of respective extracts indicated the presence of several common phytoconstituents in the two species. The antidiabetic potential was determined by using glucosidase inhibition assay while antioxidant potential was determined by using DPPH radical scavenging assay. The results showed that S. barunensis extracts had higher antioxidant activity compared to S. multicaulis extracts, while the extracts of both species had similar antidiabetic activity. This shows the possibility of using S. barunensis as a substitute to S. multicaulis. Similarly, other alpine species of Swertia may also possess such activities and should be studied to unravel their therapeutic potential.